Orbital Trapdoor Facture in Child: More Predictable Outcomes and Less Consequences - Guerra, Raphael Capelli [UNESP]; Pulino, Bianca F Borim; Mendes, Bruno Coelho [UNESP]; Pereira, Rodrigo Dos Santos; Pinheiro, Flávia Lima; Hochuli-Vieira, Eduardo [UNESP] (Wolters Kluwer, 2020)
Orbital trapdoor fractures are characterized by tissue entrapment between the fractured bone fragment and the remnant of the orbital floor. This entrapment can result in immediate local and systemic complications and poor outcomes when approached late. This article presents the case of an orbital floor fracture in a child with dystopia, pain, edema and entrapment of the inferior rectus muscle and consequent limitation of ocular motility. The strategy proposed in the early approach to orbital floor reconstruction and release of incarcerated tissue allowed the patient to achieve satisfactory results without morbidity, as compared to the outcomes of corrective sequel surgery.